1999
DOI: 10.1093/oxfordjournals.aje.a009880
|View full text |Cite
|
Sign up to set email alerts
|

Nausea during Pregnancy and Congenital Heart Defects: A Population-based Case-Control Study

Abstract: The authors investigated the possible association between a mother's nausea during pregnancy and her child's risk for a congenital heart defect using data from the population-based Atlanta Birth Defects Case-Control Study conducted in 1982-1983. Case infants (n = 998) had nonsyndromic congenital heart defects and control infants (n = 3,029) had no congenital defects. Nausea during pregnancy (NP) was graded in eight levels of "severity" based on its onset, frequency, and duration. Level 1, the most severe NP, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 21 publications
2
43
2
Order By: Relevance
“…Specifically, case-control studies provide no consistent indication that maternal use of Bendectin during the first trimester of pregnancy increases the risk of congenital heart disease. 36,80,145,146 …”
Section: Composite Drugsmentioning
confidence: 99%
“…Specifically, case-control studies provide no consistent indication that maternal use of Bendectin during the first trimester of pregnancy increases the risk of congenital heart disease. 36,80,145,146 …”
Section: Composite Drugsmentioning
confidence: 99%
“…Comparing women with the most severe level of NVP to those with no NVP, the association between CHD and using any antinausea medication was protective with a relative risk estimate of 0.74 (95% CI: 0.56-0.97). Considering specific CHD subtypes, all associations among women with NVP, comparing those who took medications with those who did not, were below the null (but not statistically significant), with the exception of tetralogy of Fallot, which was greater than 1.0 (OR: 2.19; 95% CI: 0.39-22.32), based on 8 cases, 6 of whom took medication to treat NVP, compared with 2 who did not take medication 39 .…”
Section: Resultsmentioning
confidence: 80%
“…Four studies analyzed antihistamines in the aggregate only 36-39 , the remainder reported aggregated analyses in addition to analyses of specific antihistamines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviewing all epidemiology studies on doxylamine, it is clear that while many studies show no increase in risk, a majority show some increase in risk compared with non-treatment [102][103][104][105][106][107][108][109][110][111][112][113][114].…”
Section: Discussionmentioning
confidence: 99%